The Analysis Of The Impact Of Price, Product, And Accessibility On Consumer Purchase Decisions In Online And Offline Services At Pharmacies In Bekasi City - Taufit Julianto; Delina Hasan; Derriawan Derriawan (SEAN Institute, 2024)
The advancement of technology and the increasing demand for convenience among consumers have prompted pharmacy business players to develop online-based services. This study aims to analyze the impact of price, product, and accessibility on purchasing decisions for medications in online and offline pharmacy services in the Bekasi City area. Using a quantitative approach, this study collected data through questionnaires distributed to 200 respondents, consisting of users of both online and offline pharmacy services. The analytical techniques used include Pearson correlation and Mann-Whitney U test. The results of the Pearson correlation test indicate that price has a moderate impact on consumer purchasing decisions with an r value of 0.562, product has a strong impact with an r value of 0.768, and accessibility has a moderate impact with an r value of 0.478. The Mann-Whitney U test shows no significant difference between price and accessibility in online and offline pharmacies, while a significant difference was found in product availability, with a p value of 0.0466. This study concludes that price and accessibility can influence consumer purchasing decisions, though with moderate impact, while the availability of a wider range of products, particularly in online pharmacies, has a greater influence on purchasing decisions.